Decolonising Ethics : considerations of power, politics and privilege in Aotearoa/New Zealand - Boulton, Amohia (Southern African Journal of Social Work and Social Development, 2018)
Indigenous peoples across the world have a shared experience of colonisation; a process that has resulted in war, disease and the decimation of their lands, homes and peoples. In New Zealand, the effects of colonisation are still evident with Māori (the indigenous people of New Zealand) experiencing poorer outcomes compared with non-Māori citizens across a range of social, health and well-being indicators. This paper is a case study of work being done in New Zealand, which may have resonance with work in South Africa, and other countries with a history of colonisation. It begins with a brief history of the impacts of colonisation on Māori before considering the concept of decolonisation. The author outlines the work her organisation does as an independent, tribally owned, Māori health research centre to advance a decolonisation agenda. Reflecting on their emancipatory and democratising ambitions as researchers provides the opening for a discussion about indigenous ethics. The paper presents a number of Māori ethical principles that guide their work, arguing that were such principles applied in the development and implementation of social policy and legislation, the effect would be a fairer, more equitable policy that better meets the needs of Māori as citizens. Recent legislation enacted to improve New Zealand’s care and protection system for children is discussed to illustrate the need for greater consideration of Māori values when developing legislation that directly impacts Māori. The paper concludes with a challenge to policymakers, practitioners, academics, and researchers alike to actively contribute to an agenda of liberation, emancipation and decolonisation for indigenous peoples.
Keywords: Care and protection; Care ethics; Decolonisation; Indigenous ethics; Māori; Self-Determination

Technically political: The post-politics (?) of the New Zealand emissions trading scheme - Driver, Elizabeth; Parsons, Meg; Fisher, Karen (Geoforum, 2018)

Colonization, whenua and capitalism: experiences from Aotearoa New Zealand - Moewaka Barnes, Helen; Eich, E.; Yessilth, S. (Continuum, 2018)
The English Laws Act, passed in 1858, declared the Laws of England applicable in New Zealand and cemented the hitherto alien ideology of land as property. Part of this ideology was the separation of tangata from whenua along with the separation of ownership of land from ownership of water. Māori, as tangata whenua – people of the land, made no such distinctions. Ownership affects how people ‘manage’ whenua (land), make decisions and account to the legal system. Under English law, financial considerations are at the forefront. In contrast, Māori kaitiakitanga values are concerned with the interests of land, understanding that the best interests of people will follow. Despite stark contrasts between the ideology of land as property and the ethics of kaitiakitanga – obligation, sustainability and nurture – Māori engage with mainstream agencies and lead by example in efforts to promote the wellbeing of people and environments in a unified approach. This paper outlines competing paradigms, changing relationships and challenges faced by communities who seek to nurture and respect whenua in the face of colonization. Interview data from Māori involved in community land-based initiatives illustrates past and present struggles and what some possibilities might be for the future.
Keywords: capitalism; colonisation; crown law; kaitiakitanga; whenua

Mātauranga Māori: shaping marine and freshwater futures - Clapcott, Joanne; Ataria, Jamie; Hepburn, Chris; Hikuroa, Dan; Jackson, Anne-Marie; Kirikiri, Rauru; Williams, Erica (New Zealand Journal of Marine and Freshwater Research, 2018)
Keywords: freshwater futures; marine futures; mātauranga māori; policy making; resource development

Whakamanahia Te mātauranga o te Māori: empowering Māori knowledge to support Aotearoa’s aquatic biological heritage - Ataria, James; Mark-Shadbolt, Melanie; Mead, Aroha Te Pareake; Prime, Kevin; Doherty, Jim; Waiwai, James; Ashby, Tohe; Lambert, Simon; Garner, Gary Owen (New Zealand Journal of Marine and Freshwater Research, 2018)
As Aotearoa New Zealand grapples with developing solutions to complex issues surrounding its unique freshwater and marine biological heritage, there is a growing recognition that mātauranga Māori can be ‘unlocked’ and used with great effect alongside western science. Examples where appropriate consideration and development of robust methodologies for the application of mātauranga Māori coexisting alongside western science are increasing. Unfortunately, despite the benefits that can be derived from this collaboration, the quality of engagement is not always satisfactory often due to poor interpersonal relationships and misidentification of the knowledge holders. By providing an appropriately historical context, this article is able to consider the critical issues now facing mātauranga and the Māori knowledge holders today, and fundamental requirements that will empower application of this knowledge within bio-heritage management. We consider how the development of a methodology between mātauranga Māori holders and potential end-users might contribute to improved outcomes for Aotearoa’s biological heritage.
Keywords: environmental management; indigenous rights; mātauranga māori; sovereignty; tiriti o waitangi/treaty of waitangi; whakapapa

Behind the smoke and mirrors of the Treaty of Waitangi claims settlement process in New Zealand: no prospect for justice and reconciliation for Māori without constitutional transformation - Mutu, Margaret (Journal of Global Ethics, 2018)
Governments in New Zealand have legislated a large number of settlements extinguishing many hundreds of claims taken by Māori against the Crown for breaches of the country’s founding document, Te Tiriti o Waitangi. They portray settlements as a great success for Māori and the Crown. Māori disagree. Settlements are government-determined and imposed on Māori using a smoke and mirrors approach that masks successive governments’ true intentions: to claw back Māori legal rights; to extinguish all claims; and to maintain White control over Māori. In short, to uphold the Doctrine of Discovery in further breach of Te Tiriti o Waitangi. Māori claimants and negotiators report being enticed into the process by false promises only to become traumatised and disenchanted. Yet many take a pragmatic stance and sign settlements, making the best they can out of a bad deal that goes nowhere near compensating for their actual loss. They know that despite what legislation may say, the settlements are not full, not fair and not final and that, like all previous settlements, they will be revisited. They also know that unless fundamental changes are made to the constitutional makeup of the country, there is no prospect of justice and reconciliation for Māori.
Keywords: colonisation; constitutional transformation; doctrine of discovery; kāwanatanga; tiriti o waitangi/treaty of waitangi; trauma; treaty settlements; waitangi tribunal

Māori issues 2016-2017 - Mutu, Margaret (2018)
https://catalogue.library.auckland.ac.nz/primo-explore/fulldisplay?docid=uoa_alma21140132640002091&context=L&vid=NEWUI&search_scope=Combined_All&tab=combined&lang=en_US

Diverting the Sword of Damocles: Why Did the Crown Choose to Settle Māori Historical Treaty Claims? - McDowell, Tiopira (Australian Journal of Politics & History, 2018)
Keywords: crown; treaty settlements

The Crown: Is It Still ‘White’ and ‘English-Speaking’? - Godfery, Morgan (The Round Table, 2018)
‘There is a need for a mindset shift away from the pervasive assumption that the Crown is Pākehā, English-speaking, and distinct from Māori’, wrote the permanent commission of inquiry investigating breaches of New Zealand’s founding document, the Treaty of Waitangi. ‘Increasingly, in the twenty-first century, the Crown is also Māori.’ This paper argues that ‘the Crown in right of New Zealand’ is in need of redefining. In the 19th and parts of the 20th century Māori leaders and institutions were often understood as separate from the Crown. But that understanding is shifting, and this paper argues the shift is leading to a new understanding of the Crown in right of New Zealand.
Keywords: crown; kāwanatanga; kīngitanga; rangatiratanga

How should we teach about Te Tiriti o Waitangi? Issues for raraunga (citizenship) education - Bargh, Maria; Macfarlane, Angus (Our Civic Future, 2018)
Keywords: colonisation; policy; tiriti o waitangi/treaty of waitangi

Māori political and economic recognition in a diverse economy - Bargh, Maria (The Neoliberal State, Recognition and Indigenous Rights, 2018)
Keywords: iwi enterprises; tino rangatiratanga

Māori, a politicized identity: Indigenous identity, voter turnout, protest, and political party support in Aotearoa New Zealand - Greaves, Lara M.; Sengupta, Nikhil K.; Townrow, Carly S.; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2018)
Political struggles are important to the identities of many indigenous peoples. This article examines identity as a predictor of crucial political outcomes—voter turnout, support for protest, and political party support—for Māori, the indigenous peoples of Aotearoa (New Zealand). We analyzed data from a national probability sample of Māori (N = 663) that included a scale of subjective identification with various aspects of Māori identity: the Multidimensional Model of Māori Identity and Cultural Engagement. Use of the scale allowed us to examine the facets of ethnic identity that predict political mobilization for indigenous peoples. As expected, the identity domain relating to political struggle, Socio-Political Consciousness, was positively associated with support for left-wing parties and Māori rights protest but negatively associated with support for the right-wing party. However, Socio-Political Consciousness did not relate to voter turnout. These results demonstrate the importance of ethnic identity as a key predictor of political behaviors for indigenous peoples. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; ethnic identity; kāwanatanga; political participation; political parties; voter turnout; voting

A Māori perspective of being and belonging - Rameka, Lesley (Contemporary Issues in Early Childhood, 2018)
Belonging and being are inextricably linked. From a M?ori perspective, belonging and being can be viewed through a number of interconnected historical and contemporary frames. One frame is derived from M?ori perceptions of the creation of the universe and genealogical relationships to the universe and everything in it. Another frame of belonging and being stresses increasingly diverse and complex positionings that require negotiation of radically different terrains of assumptions, behaviours, values and beliefs. This article explores two interrelated aspects of being and belonging from a M?ori perspective: whakapapa (?genealogical connections?) and whanaungatanga (?family relationships?). It discusses how each aspect has changed over time as a result of colonisation, urbanisation and western education, and identifies how the reflection of each has been transformed.
Keywords: belonging; colonisation; education; urbanisation; whakapapa; whanaungatanga

Conceptualising historical privilege: the flip side of historical trauma, a brief examination - Borell, Belinda; Moewaka Barnes, Helen; McCreanor, Tim (AlterNative: An International Journal of Indigenous Peoples, 2018)
Historical trauma is an important and growing area of research that provides crucial insights into the antecedents of current-day inequities in health and social wellbeing experienced by Indigenous people in colonial settler societies. What is not so readily examined is the flip side of historical trauma experienced by settlers and their descendants, what might be termed ?historical privilege?. These historic acts of privilege for settlers, particularly those emigrating from Britain, provide the antecedents for the current-day realities for their descendants and the structural, institutional and interpersonal levels of advantage that are also a key feature of inequities between Indigenous and settler. This article theorises an explicit link between historical trauma and historical privilege and explores how the latter may be examined with particular reference to Aotearoa New Zealand. Three core elements of historical trauma are posited as a useful framework to apply to historical privilege.
Keywords: colonisation; trauma

(C)ELSI‐us: Reducing friction with indigenous communities in genomic research - Hudson, Maui; Wilcox, Phillip; Smith, Barry; Beaton, Angela; Milne, Moe; Russell, Khyla (American Anthropologist, 2018)
As government policy settings have become more responsive to aspirations of Indigenous communities and researchers are more sensitive to the concerns of Indigenous communities, the research environment has become more conducive to understanding the cultural implications of genomic research. CELSI-us is a tongue-in-cheek reference to taking the temperature of the relationship between genomic researchers and Indigenous communities. If we create friction, then the temperature rises. But if we engage in a culturally responsive manner, then we take the heat out of the relationship and can focus on achieving mutually beneficial outcomes. This has been the focus of our work to date, and we hope that the guidelines we have produced make this challenging path easier for others to traverse.
Keywords: data; indigenous data

Indigenous data and health: critical research approaches and indigenous data governance - Reid, Papaarangi; Kukutai, Tahu; Cormack, Donna (European Journal of Public Health, 2018)
Background and objectives:‘Race’ and ethnicity data have become increasingly institutionalised within health research about indigenous peoples. While these data are critical to monitoring the differential distribution of risks and benefits in racialised societies, their uncritical and under-theorised use can perpetuate harmful biologically-deterministic and essentialist approaches to indigenous health. Additionally, indigenous rights and interests in data about us are often overlooked, with issues of indigenous data governance unresolved. The workshop objectives are to: Develop skills to critique uncritical use of ‘race’/ethnicity in indigenous health researchProvide examples from Aotearoa/New Zealand of frameworks or principles of indigenous data sovereignty
Keywords: data; health; indigenous data sovereignty

Census 2018 and Implications for Māori - Kukutai, Tahu; Cormack, Donna (New Zealand Population Review, 2018)
The population census is a universal tool of governance but has come under increasing pressure as governments look to reduce costs, gain efficiencies and counter declining response rates. In Aotearoa New Zealand, the census transformation strategy has a short-term focus on modernising the census and a long-term vision of a fully administrative census. The digital-first 2018 Census was an ambitious step towards modernisation but there are growing concerns that it may fail to deliver high-quality data, particularly for Māori and iwi. This research note considers the implications of lower response rates and reflects on the steps that might be taken to retain the trust and confidence of Māori in the census, including possibilities for Māori data governance across the official statistics system.
Keywords: census; data collection; governance; methodology; population; population studies; sovereignty; transformation

The geography of deprivation in New Zealand by electorate - Exeter, Daniel J.; Crengle, Sue; Cavadino, Alana; Greaves, Lara; Zhao, Jinfeng; Lee, Arier; Browne, Michael (Kōtuitui: New Zealand Journal of Social Sciences Online, 2018)
In the run-up to the 2017 General Election, the economy, housing, health, education, inequality and justice were important policy issues. General Elections are a time when voters exercise their democratic right to vote for their preferred party and parliamentary candidate to represent themselves, their whānau and community. In many cases, political parties’ policies seek to improve the wellbeing of people who are living in more deprived communities, but people in deprived communities are typically less likely to vote. The recently released New Zealand Index of Multiple Deprivation (IMD) enables users to explore deprivation in electorates across the country. This paper compares the distribution of deprivation and voter turnout across a selection of General Electoral Districts (GEDs) and demonstrates that while overall patterns of deprivation may be similar between GEDs, the drivers of these patterns can differ immensely.
Keywords: Inequity; disparities; elections; electorates; voter turnout